THE DYNAMICS OF PINISI PRESERVATION IN THE FLOW OF GLOBALIZATION AND SOCIO-CULTURAL CHANGE - Fikri, Muhammad; Adrian, Adrian; Fajri Al Hakim, Winanda; Mut Mainnah, Sitti; Mutaallif, Sardil; Merdekawati Djafar, Eka; Rezky Zulkarnain, Muh. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research examines the problem of preserving the Pinisi Ship as Indonesia's maritime cultural heritage that faces serious pressures due to modernization and globalization. The main problem in this research lies in the declining regeneration of craftsmen, limited raw materials, shifting cultural values, weak legal protection, and the lack of involvement of the younger generation in maintaining the sustainability of the Pinisi Shipbuilding tradition. The purpose of this research is to analyze the main obstacles to the preservation of the Pinisi Ship and formulate strategies and innovations that can be applied to strengthen its existence in the midst of the times. This research uses a descriptive qualitative method with a literature study approach, which utilizes secondary data in the form of scientific journals, academic books, policy documents, and publications of relevant cultural institutions. Data collection techniques were conducted through documentation, while data analysis used content analysis to identify key themes related to preservation challenges and opportunities. The results show that Pinisi Ship preservation requires an integrative approach that includes strengthening local culture-based education, legal protection of cultural heritage, utilization of digital technology for documentation and promotion, and development of sustainable cultural tourism. The conclusion of this research confirms that the sustainability of the Pinisi Ship can only be realized through synergy between the government, the community, and the local community. The conclusion of this study confirms that the sustainability of the Pinisi Ship can only be realized through synergy between the government, local communities, and the younger generation in maintaining cultural values while adapting them adaptively to social and economic changes.